Coping Mechanism Versus Health-Related Quality of Life (HRQoL) Among Methadone Maintance Treatment (MMT) Program Participants - Lua , Pei Lin (International Journal of Psychosocial Rehabilitation, 2013)
There is evidence that coping strategy could be associated with health-related quality of life (HRQoL) among people with life threaten- ing illnesses. However, such information from opioid abusers is still insufficient and limited. This study aimed to 1) describe the overall HRQoL status and preferred coping strategies, 2) correlate between HRQoL and coping mechanisms and 3) compare coping strategies of patients with different HRQoL levels. A convenient sample of opiate abusers from seven Methadone Maintenance Treatment (MMT) centres in East Coast of Peninsular Malaysia was enrolled. The Malay Brief COPE and WHOQOL-BREF were administered to evaluate coping strategies and HRQoL status. Data was analysed using descriptive and non-parametric statistics (SPSS 16). Sixty patients parti- cipated (mean age=34.7 years; < 15 years of addiction=51.7%; employed=91.7% and rural residents=65.0%). Overall, they fared the best physically but reported worse HRQoL in Environmental issues. Religion was the most preferred coping strategy (83.4%). Signific- ant positive associations between Overall HRQoL versus Religion and Planning were detected (rs=+0.34, p